2021
DOI: 10.21162/pakjas/21.480
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Sitophilus oryzae infestation on amylose content and weight loss of eight rice varieties

Abstract: Sitophilus oryzae is one of the primary pests that causes severe damage to food products. Damage of the grains cause a drastic dropping of rice quality, which significantly affected our rice industry. The amylose content and weight loss are two components that are affected due to the S. oryzae infestation. In this study, eight rice varieties namely Thai Pathumthani Fragrant White Rice 100%, Vietnam Long Grain White Rice 5%, Pakistan Basmathi Long Grain White Rice PK 385, Indian Steam Pusa 1121 Basmathi LGWR, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This finding similar to [33], [34] reported that Cigarette beetle as main insect of coriander and fennel plant during storage. Insect pests promote weight loss of the product stored, a very important factor, causing nutritional value loss, commercial loss, as well as quality degradation [35]. The obtained results in Table 4 show the first appearance and degree of pest infestations in different package types during six month of storage indicated that Polyethylene package have high tolerance of insect infestation comparing with other types.…”
Section: Resultsmentioning
confidence: 92%
“…This finding similar to [33], [34] reported that Cigarette beetle as main insect of coriander and fennel plant during storage. Insect pests promote weight loss of the product stored, a very important factor, causing nutritional value loss, commercial loss, as well as quality degradation [35]. The obtained results in Table 4 show the first appearance and degree of pest infestations in different package types during six month of storage indicated that Polyethylene package have high tolerance of insect infestation comparing with other types.…”
Section: Resultsmentioning
confidence: 92%
“…The importation of white milled rice, its storage and retailing conditions, like packaging material, relative humidity and temperature might be favorable to the increases in grain moisture content, the development of colored grains, molds development and insect infestation. The consequence of insect infestation of cereal grains during storage is damage and huge quantitative losses that are also linked to economic, nutritional and quality losses [48]. The low level of insects in parboiled rice and the complete absence in domestic parboiled samples might be explained by the fact that parboiling heals the crevices on grains and further hardens the rice starch following gelatinization, rendering the grains resistant to insect invasion.…”
Section: Discussionmentioning
confidence: 99%
“…S. oryae and S. cerealella have been found to cause more damage (Mason et al, 2012). Through this loss of nutritional value, commercial loss as well as quality deterioration of wealth, and there is a possibility of developing grain spoilage due to an increase in temperature and water content of grain stock due to insect activity (Adler et al, 2007;Zulaikha et al, 2021). Meanwhile, the use of fumigating chemicals, mainly fumigants, during storage is common worldwide, but their excessive use causes environmental problems and risks to human health (Lee et al, 2003;Chou et al, 2022).…”
Section: Post-harvest Handlingmentioning
confidence: 99%